Ambient and Artificial Intelligence in Therapeutics - Hannah Alex (Current Overview on Science and Technology Research Vol. 9, 2022)
A brand-new approach to a technology called Ambient Intelligence (AmI) aims to empower people by creating a digital environment that is emotional-responsive, adaptable, and sensitive to their feelings, gestures, habits, and needs. The surroundings and position of the user are known to this environment. The most ambitious representation of AmI is Intelligent Mixed Reality (IMR), an improvement above conventional virtual reality environments. With the help of IMR, computer interfaces may be seamlessly incorporated into the physical world, allowing users to communicate and interact with their surroundings in a way that feels intuitive and natural. What effects will the adoption of the AmI paradigm have on medical care? The study emphasizes the relational and technological aspects of AmI to demonstrate its potential applications in healthcare. Medical professionals must pay close attention to human elements, project management, ergonomics, technology, and the relevant health service’s institutional demographic structure to fully exploit the potential of AmI.